Analisis Perancangan Sistem Pendukung Keputusan Penerima Beasiswa Menggunakan Metode Multi Factor Evaluation Process - Ristiani, Dewi; Adiyanto; Asbari, Masduki; Novitasari, Dewiana (Journal of Industrial Engineering & Management Research, 2020)
The College of Information Management and Computer Insan Pembangunan is a private B Accredited university, which was founded in 2002 based on the Decree of the Minister of National Education and until 2019 has had 3 (three) study programs namely Information Systems, Accounting Information Systems and Information Technology. Every year, College of Information Management and Computer Insan Pembangunan also distributes scholarships to students. One of the scholarships that was distributed was the Academic Achievement Improvement scholarship. Scholarships to improve academic performance are awarded by the Ministry of Research, Technology and Higher Education. In organizing the process of distributing scholarships to increase academic achievement by of Information Management and Computer Insan Pembangunan to students, it includes a registration process carried out by students, then a selection is carried out by Puket III and the College of Information Management and Computer Insan Pembangunan leaders when the PPA scholarship applicant quota is met. The selection process for PPA scholarship recipients at College of Information Management and Computer Insan Pembangunan has not applied the DSS (Decision Support System) method and is only based on quotas, so that there is a lack of consideration for students who are entitled to receive academic achievement improvement scholarships and are somewhat less targeted and less objective in terms of assessment, while the enthusiasm of students who want to get a academic achievement improvement scholarships is quite large. The DSS method used by the author is the Multi Factor Evaluation Process (MFEP) method, which is a method used to determine the order of assessments from several predetermined factors. The factors used in the academic achievement improvement scholarships selection are GPA, parents' income, award certificates and the activeness of student organizations. The use of SPK with MFEP can help College of Information Management and Computer Insan Pembangunan in the selection process that is right on target and more objective.